Pembangunan Sumber Daya Manusia Sektor Teknologi di Papua Pegunungan - Teguh Priyantoro; Esibius Irwan Hisage; Manuel Gombo (Ikatan Ahli Informatika Indonesia, 2025)
Human resource development is an integral part of the development of a region or area. As a new autonomous region, Papua Pegunungan requires various effective regional development strategies to align development and equitable distribution of community welfare in accordance with the objectives of regional expansion. Rapidly developing technology currently demands the availability of competent human resources, especially in the technology sector. This study aims to analyze the need for these human resources, tailored to the types of jobs in the technology sector that are predicted to be highly needed in regional development in Papua Pegunungan. The results of the study indicate that there are at least eight areas of focus in human resource development in the technology sector in Papua Pegunungan.